Using Some Transformations for Solving a Type of Fractional Differential Equations - Istabraq Ismaeel Fadhil; Muayyad Mahmood Khalil; Nihad Shareef Khalaf (Genius Journals, 2022)
In this article, we presented a new exact solution for Fractional Riccati Differential Equation FRDE
Keywords: Fractional Riccati Equation,; Integral Condition; Exact Solution